Impact of the invasive tree black locust on soil properties of Mediterranean stone pine-holm oak forests - De Marco, Anna; Arena, Carmen; Giordano, Maria; De Santo, Amalia Virzo (PLANT AND SOIL, 2013)
Invasion by N-2-fixing species may alter biogeochemical processes. We hypothesized that the grade of invasion by the N-2-fixer black locust (Robinia pseudoacacia L.) could be related to the distribution and pools of carbon (C) and nitrogen (N) along the profile of two Mediterranean mixed forests of stone pine (Pinus pinea L.) and holm oak (Quercus ilex L.). A low-invaded (LIN) and a high-invaded (HIN) mixed forest were studied. We assessed: N concentration in green and in senescent leaves; C and N pools along the soil profile; seasonal changes of soluble C and N fractions, and microbial activity. Compared to coexisting holm oak and stone pine, black locust had higher N content in green and in senescent leaves. In the mineral soil: N stocks were similar in LIN and HIN; water soluble C and microbial activity, were lower in HIN compared to LIN; water soluble N showed seasonal changes consistent with tree growth activity in both HIN and LIN. In the organic layer of HIN, C and N stocks were about twofold larger than expected on the basis of stand density. Black locust increased C and N stocks in the upper organic layers that are more vulnerable to disturbance. However, it did not increase N stocks in the mineral soil.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: C and N stocks; Exotic N-2-fixing tree; litter; organic layer and mineral soil; Water soluble C and N